Closed Genome Sequence of Phytopathogen Biocontrol AgentBacillus velezensisStrain AGVL-005, Isolated from Soybean - Pylro, Victor Satler; Dias, Armando Cavalcante Franco; Andreote, Fernando Dini; Morais, Daniel Kumazawa; Varani, Alessandro de Mello; Andreote, Cristiane Cipolla Fasanella; Bernardo, Eduardo Roberto de Almeida; Zucchi, Tiago (Genome announcements, 2018)
We report here the closed and near-complete genome sequence and annotation ofBacillus velezensisstrain AGVL-005, a bacterium isolated from soybean seeds in Brazil and used for phytopathogen biocontrol.